2001
DOI: 10.1364/ao.40.003784
|View full text |Cite
|
Sign up to set email alerts
|

Absolute autofluorescence spectra of human healthy, metaplastic, and early cancerous bronchial tissue in vivo

Abstract: Autofluorescence is emerging as a useful tool for the detection of early cancers in the bronchi. It has already produced interesting results, which have been implemented in commercial imaging devices. Their design relies on the spectroscopy of the tissues of interest. However, a large majority of these autofluorescence spectroscopy studies have been presented in arbitrary units. This is a drawback for, in particular, the designing of imaging devices based on autofluorescence. Using correction factors and a spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 36 publications
3
46
0
3
Order By: Relevance
“…After correcting the effects of probe-tissue distance and intensity variation of excitation, it has been found that the normal bronchial tissue exhibits slightly stronger emission than the dysplasia tissue with nearly identical spectral shapes, while those of the cancerous ones were much weaker than both tissues. [56] Similar in vivo study of emission ratio differences has also been reported for distinguishing nasopharyngeal carcinoma and normal tissue. [57] The similarity in the shapes of emission spectra between the normal and cancerous tissues significantly reduces the reliability of this technique for cancer detection.…”
Section: Spectroscopy Measurementssupporting
confidence: 62%
“…After correcting the effects of probe-tissue distance and intensity variation of excitation, it has been found that the normal bronchial tissue exhibits slightly stronger emission than the dysplasia tissue with nearly identical spectral shapes, while those of the cancerous ones were much weaker than both tissues. [56] Similar in vivo study of emission ratio differences has also been reported for distinguishing nasopharyngeal carcinoma and normal tissue. [57] The similarity in the shapes of emission spectra between the normal and cancerous tissues significantly reduces the reliability of this technique for cancer detection.…”
Section: Spectroscopy Measurementssupporting
confidence: 62%
“…The system is completed with a standard video cassette recorder [11]. In recent studies, the addition of a 3.5 mm spacer, fitted at the distal end of the DAFE1 endoscope, ensures that all autofluorescence spectra are taken with the fibre-bundle tip at the same distance from the mucosa surface [12], and that a balance is achieved between two antagonist effects, namely an increase in the probe-sample distance to minimise the geometrical distortion of the spectra and a decrease in this distance to maximise the signal-to-noise ratio [13].…”
Section: The Videothoracoscopic Autofluorescence Imaging Devicementioning
confidence: 99%
“…Sabe-se que a água está envolvida em todos os eventos biológicos, inclusive no processo de cicatrização. A habilidade de reparo a injúrias foi avaliada, baseando-se no registro da fluorescência nativa da pele (Stamatas et al, 2006 (Andersson et al, 1987;Kennedy et al, 1996;Svanberg et al, 1998;Zellweger et al, 2001). ALA é um composto endógeno que participa da síntese do heme e, em excesso, leva ao acúmulo intracelular da protoporfirina IX (AngellPetersen et al, 2007) que pode ser ativada com luz visível (Juzenas et al, 2002b).…”
Section: Cicatrização Da Peleunclassified
“…Sabe-se que a mesma é ativada por luz de comprimentos de onda na faixa de 400 a 410 nm e emite fluorescência em dois picos, um na faixa de 630-40 nm e o outro na faixa de 700-10 nm (Zellweger et al, 2001;Juzenas et al, 2002b).…”
Section: Cicatrização Da Peleunclassified
See 1 more Smart Citation